2022
DOI: 10.1007/s40145-022-0611-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term ceramic matrix composite for aeroengine

Abstract: Three strategies were proposed to prolong the service life of continuous fiber-reinforced silicon carbide ceramic matrix composite (CMC-SiC), which served as thermal-structure components of aeroengine at thermo-mechanical-oxygenic coupling environment. As for some thermal-structure components with low working stress, improving the degree of densification was crucial to prolong the service life, and the related process approaches were recited. If the thermal-structure components worked under moderate stress, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(17 citation statements)
references
References 154 publications
0
17
0
Order By: Relevance
“…Due to the ability to operate at high temperature with high strength and toughness, continuous fiber-reinforced ceramic matrix composites (CMCs) are commonly used for thermal structural parts in the turbine engine, fusion reactors, and gas-cooled fast reactors, [1][2][3][4][5][6][7] and in some cases become irreplaceable with further increasing the service temperature. Particularly, CMCs are not only insensitive to cracks, but also have a much lower density than typical superalloys.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the ability to operate at high temperature with high strength and toughness, continuous fiber-reinforced ceramic matrix composites (CMCs) are commonly used for thermal structural parts in the turbine engine, fusion reactors, and gas-cooled fast reactors, [1][2][3][4][5][6][7] and in some cases become irreplaceable with further increasing the service temperature. Particularly, CMCs are not only insensitive to cracks, but also have a much lower density than typical superalloys.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon carbide (SiC) is one of the promising candidates for advanced nuclear systems, aerospace, and the third‐generation semiconductor applications, due to its excellent high‐temperature mechanical properties, outstanding chemical stability, and remarkable irradiation‐damage‐resistance 1–9 . However, it is difficult to fabricate large size SiC‐based components with complex shapes due to their poor machinability 10–11 .…”
Section: Introductionmentioning
confidence: 99%
“…Various strategies have been proposed to enhance the mechanical properties of these ceramics, such as adding fibers and reinforcement phases, but most are too expensive and challenging to integrate into ceramic industries. [7][8][9] Zhong et al 10 demonstrated the effective improvement of mechanical properties for ceramic tiles using in situ mullite whiskers. Xiao et al 11 found that in situ mullite whiskers could be generated by strictly controlling the raw material ratio, making them suitable for preparing high-strength ceramic tiles in industrial manufacturing.…”
Section: Introductionmentioning
confidence: 99%